1970
DOI: 10.1017/s0025315400004975
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Variation of the Free and Combined Dissolved Amino Acids in the Irish Sea

Abstract: A study has been made of the seasonal variation of the free and combined amino acids at a station in the southern Irish Sea. The principal amino acids found were alanine, serine, glycine, threonine and valine. Acidic amino acids were generally present at lower levels and basic amino acids were usually below the detection limit. The variations observed for the free amino acids were small compared with those of the combined acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 17 publications
(5 reference statements)
3
38
0
Order By: Relevance
“…In shallow estuaries, their occurrence is only partly reflected in chlorophyll a concentrations and in phytoplankton cell density, whereas macrophyte and sediment surface appeared as the major sources (Jerrgensen, 1982;Macko and Green, 1982). In open waters, the situation differs and increases of DFAA concentrations during, or following, periods of high primary production are sometimes reported (Wood, 1966;Riley and Segar, 1970;Crawford et al, 1974). Excretion of nitrogen compounds by various organisms, including zooplankton crustaceans, may also contribute to the addition of non-algal amino acids (Webb and Johannes, 1967;Lampert, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…In shallow estuaries, their occurrence is only partly reflected in chlorophyll a concentrations and in phytoplankton cell density, whereas macrophyte and sediment surface appeared as the major sources (Jerrgensen, 1982;Macko and Green, 1982). In open waters, the situation differs and increases of DFAA concentrations during, or following, periods of high primary production are sometimes reported (Wood, 1966;Riley and Segar, 1970;Crawford et al, 1974). Excretion of nitrogen compounds by various organisms, including zooplankton crustaceans, may also contribute to the addition of non-algal amino acids (Webb and Johannes, 1967;Lampert, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…(4) Several studies of amino acid abundance in seawater showed that the composition of the amino acid pool is relatively constant and glutamic acid represents 5 to 13% of the total pool (Siegel and Degens, 1966;Riley and Segar, 1970;Clark, 1972;Daumas, 1976;Williams eta[., 1976;Billens et ak, 1980;Dawson and Gocke, 1980). Using these assumptions and estimates of heterotrophic activity, the maximum estimated contribution of bacteria to NH4 regeneration was 25% with an average 16% for spring and summer (Table 3 C).…”
Section: Discussionmentioning
confidence: 99%
“…This hydrocarbon may be produced from an abundant phytoplankton that DOC increased during the spring phytoplankton bloom. Other workers have monitored specific organic compounds such as amino acids (Riley and Segar, 1970) and hydrocarbons and fatty acids (Schultz and Quinn, 1977) in coastal regions and also noted the coincidence of specific compound level increases with phytoplankton blooms. Consequently, it would be expected that certain volatiles would increase in concentration during local spring (and fall) algal blooms (Fish, 19l1;Lillick, 1937;Yentsch and Ryther, 1959).…”
Section: Sumrymentioning
confidence: 97%